Uma contribuição para a formulação de diretrizes para elaboração do manual do usuário de edifícios - Aguilera, Camila Garcia (Universidade Federal de São Carlos, 2005)
Analyzing the existent norms, this investigation pretends to offer subsidies to collect and elaborate the information that must be include into the building user guide. In this manner, the user could accomplish correctly his functions. The focus of the research refrains from the user guide, whose objective is to transmit to the landed property s owner, in the instant of the key s delivery, the basics notions to the corrected use and maintenance of his propriety, assuring the durability, preventing damages from a bad use or the lack of conservation, and giving him a higher security and economy. For this valuation, the country s rules and legislation was analyzed, because now it claims the adoption of the manual, and norms and social behavior from other countries too, resulting in a consumer s defense movement. The work talks about constructive projects and processes used in the building sub sector and how the application of concepts and softwares can improve the satisfaction and the client s attending. The research presents too technical features like the retro alimentation and the as built project. The case study realized into this job, which consists in an interview accomplished with 11 engineers and 150 guide s users, reveals that, in spite of the consensus about the uses of the user guide, it further doesn t offers satisfactory and suitable information for it purposes. Rely on this data, the present work analyzes, comments and suggests modifications to the existents norms of the guide s elaboration serving.
Keywords: Edifícios; Construção civil; As Built; Gestão da qualidade total; Manual do usuário; User Guide; Building; As Built; Quality; Code of consumer s defense; ENGENHARIAS::ENGENHARIA CIVIL::CONSTRUCAO CIVIL